Rotorcraft-pilot couplings: analysis and detection in a safety enhancement framework - Fasiello, S.; Yu, Y.; Jump, M.; Pavel, M.D.; Kampen, E.J. van; Masarati, P. (My University, 2018)
Nowadays, the complexity of high speed civil transport and highly-augmented rotorcraft, has led to an increase in the chances of encountering unwanted unstable phenomena, such as the so called Aircraft/Rotorcraft-Pilot Couplings (A/RPCs) or Pilot-Induced Oscillations (PIOs), whose unpredictability has given rise to a serious problem concerning the safety of a mission. When talking about PIOs, McRuer defined them as "inadvertent, sustained aircraft oscillations which are a consequence of an abnormal joint enterprise between the aircraft and the pilot". However, A/RPCs, these undesirable events associated with the interaction between pilot and aircraft, have become diverse and more complex than those encountered in the past. At the moment, there are different methods available to prevent and detect Cat. I/II A/RPC, but particular interest has recently arisen in this topic for flight simulation applications as any enhancement of these tools in order to accurately and objectively predict, detect (in real-time) and alleviate RPCs will be greatly welcomed. One of the main questions to be answered through the efforts carried out within this work is related to the better detection in real-time of embedded tendencies to RPCs in modern aircraft. To answer this question, initially an assessment of the efficacy of the Phase-Aggression Criterion (PAC), which has been designed a few years ago at the University of Liverpool, will be undertaken either: as a means of alerting the pilot to conditions likely to lead to the onset of a PIO; or, given that the time available for the pilot to counteract may be extremely limited, as a means to assist him/her in alleviating (automatically) the PIO condition itself. Preliminary results from flight simulation trials to explore how best to achieve this will be reported. Moreover, this work will report on the development of PAC boundaries for more highly augmented response types. Furthermore, as classified by McRuer, Cat. III PIO, which is nonlinear in essence, is the most complex one. However, the researches on Cat. III PIO are rare. This paper will reveal some elementary results of Cat. III PIO. Since there is no existing method used for predicting and detecting Cat. III PIO, this paper utilized the characteristics of PIO, such as the amplitude, the oscillation frequency and ultimate tendency of key aircraft response states to judge Cat. III PIO preliminarily. By using this elementary judgment of PIO, we studied the following factors: time delay of pilot input and helicopter main body, actuator position saturation, actuator rate limit and SCAS control authority in triggering PIO. Results show that PIO induced by actuator position saturation, actuator rate limit and SCAS control authority can be regarded as Cat. III PIO as the variation of these factors can be viewed as a kind of transition of effective controlled vehicle dynamics. These kinds of transition can cause a mismatch between the effective controlled vehicle dynamics and pilot control strategy, which is the main cause of Cat. III PIO.